2012
DOI: 10.1111/j.1443-1661.2012.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Cap‐assisted water immersion for minimal sedation colonoscopy: Prospective, randomized, single‐center trial

Abstract: In comparison with water immersion without cap, cap-assisted water immersion colonoscopy was not able to shorten the cecal intubation time. However, it has the possibility of reducing patient discomfort and difficulty of colonoscope insertion. Potential impact on improved detection of neoplastic lesions has to be evaluated by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This method, too, comes with no additional risk. Most studies evaluating cap-fitted colonoscopy emphasized better patient comfort [ 42 , 43 , 44 ] or shorter time for cecal intubation [ 42 , 43 , 45 ], while others could not confirm these effects [ 42 , 46 ]. These data did not show an improved cecal intubation rate.…”
Section: New Colonoscopy Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method, too, comes with no additional risk. Most studies evaluating cap-fitted colonoscopy emphasized better patient comfort [ 42 , 43 , 44 ] or shorter time for cecal intubation [ 42 , 43 , 45 ], while others could not confirm these effects [ 42 , 46 ]. These data did not show an improved cecal intubation rate.…”
Section: New Colonoscopy Methodsmentioning
confidence: 99%
“…Some authors reported a significantly lower miss rate for all adenomas (21 vs. 33%; n = 100) compared with usual colonoscopy [ 47 ]. Furthermore, higher adenoma detection (mean number of detected adenomas per procedure 2.0 vs. 1.2; n = 295) was reported [ 45 ], but the majority of studies investigating this parameter did not confirm this [ 42 , 43 , 44 , 46 ] or reported lower adenoma detection [ 48 ]. These studies with an inferior or equal result represent a total of 3,684 patients.…”
Section: New Colonoscopy Methodsmentioning
confidence: 99%
“…Mizukami et al . reported on water navigation colonoscopy, which is a modified technique of water immersion discussed above, and many other studies regarding water immersion have been reported globally to date . According to a systematic review by Leung et al ., water immersion significantly reduces colonoscopy pain compared with air insufflation.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Mizukami et al [21][22][23] reported on water navigation colonoscopy, which is a modified technique of water immersion discussed above, and many other studies regarding water immersion have been reported globally to date. 24,25 According to a systematic review by Leung et al, 26 water immersion significantly reduces colonoscopy pain compared with air insufflation. In water navigation colonoscopy, with the patients in the left lateral position, injection of water at rectum and complete air removal from the rectosigmoid allows the injected water to flow straight down into the descending colon through the collapsed lumen and the sigmoid becomes short and straight.…”
Section: Introductionmentioning
confidence: 99%
“…Warm water has been suggested to decrease colonic spasm [6] and most of the published trials comparing water with air insufflation have used warm water (36-42°C). Reports of the use of cool (room temperature) water are limited [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%